Valuasi Nilai Ekonomi Langsung Hutan Mangrove sebagai Penyedia Jasa Wisata di Pulau Burung Kabupaten Tanah Bumbu - Aswat, Muhammad; Nur, Anshar (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This study aims to determine the characteristics and assessments of visitor Pulau Burung Mangrove Forest s, willingness to pay, and the travel cost method. Data collection techniques in the form of observation, interviews using questionnaires and documentation with the number of respondents as many as 75 people. The data were processed using quantitative descriptive, willingness to pay, and the travel cost method. Based on the results of the study, it is known that the characteristics and perceptions of visitors vary widely, consisting of age, regional origin, gender, marital status, education level, occupation, total income, type of vehicle, information about tourist attractions, tourist attractions, motivation, additional facilities, security, officer services, accessibility, cleanliness, entrance tickets, willingness to pay and the respondent's travel costs.The results of this study, the willingness to pay value is Rp. 28,000.00 / person. In addition, the value of the travel cost method is known to be Rp. 165,667 / person. So that in one year each value of willingness to pay, and travel cost method for tourism in Bird Island Mangrove Forest is Rp. 169,668,000.00 and Rp. 1,004,970,500.00.